INTERLEUKIN 8 BERHUBUNGAN DENGAN DERAJAT GASTRITIS PADA PASIEN TERINFEKSI HELICOBACTER PYLORI - Mariadi, IK; Kurniari, PK; Wibawa, IDN; Purwadi, N; Suryadarma, IGA (journal of internal medicine, 2011)
Helicobacter pylori infection induces a local pro-inflammatory cytokine response. The secretion of IL-8 by epithelialcells is probably a key factor in host defenses at mucosal sites, permitting a rapid polymorph response against infectious agents.Interleukin-8 is an important chemotactic and activating factor for neutrophils. If defense mechanisms fail and chronic infectionresults, continued up regulation of IL-8 and neutrophil activation could lead to mucosal damage and increased free radicalformation. Mucosal IL-8 production in Helicobacter pylori infection may be an important factor in the immunopathogenesisof gastritis and peptic ulcer disease. This study aim to investigate correlation between IL-8 and severity of gastritis in ourpopulation. We performed a cross-sectional analytic study in Helicobacter pylori infected patients. Severity of gastritis wasdetermined base on The Updated Sydney System. IL-8 level was analyzed from gastric mucosa biopsy using ELISA method.We included 65 samples. 31 (47.7%) men and the rest was women. Base on Kruskalwallis test we found significant associationbetween IL-8 gastric mucosa and severity of gastritis (x2 = 12.8; p = 0.002). We also found significant association between IL-8gastric mucosa and density of H pylori infection (x2 = 10.6; p = 0.01), severity of atrophy (x2 = 9.4; p = 0.02) and neutrophilscount (x2 = 11.0; p = 0.01). But notmethaplasia (x2 = 3.3; p = 0.18). Base on this study we concluded that IL-8 was associatedwith severity of gastritis in Helicobacter pylori infected patients.